Composite antimicrobial agent, blown film and method of preparation and use, antimicrobial biodegradable polyester composition, polyester material and method of preparation
Patent Information
- Application Number
- CN202211331368.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-28
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2042-10-28
AI Technical Summary
1)本发明提供的复合抗菌剂包含增容二元共聚微球负载抗菌金属纳米粒子,其与生物可降解树脂之间具有良好的相容性,此外,复合抗菌剂中的N-乙烯基酰胺聚合物能够保证包含上述复合抗菌剂的生物降解材料在全生命周期均具有优异的抗菌性并且具有高的抗菌效率,特别地,在遇水后不发生迁移;将其用于生物可降解材料时,能够显著提高生物可降解材料的抗菌性能和力学性能,使得生物可降解材料兼具优异的力学性能、抗菌性能和生物降解性能。
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_6
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymers, specifically to a composite antibacterial agent and its preparation method and application, an antibacterial biodegradable polyester material and its preparation method, an antibacterial biodegradable polyester material and its preparation method, and an antibacterial biodegradable polyester blown film and its preparation method and application. Background Technology
[0002] In recent years, with the improvement of living standards and the enhancement of hygiene awareness, the market demand for antibacterial materials and products has continued to expand. Among them, antibacterial plastic products account for a large proportion. Various household products, including refrigerators, air conditioners, various food containers, packaging bags, washing machines, toys, vacuum cleaners, etc., all use various thermoplastic antibacterial plastics.
[0003] The preparation of antibacterial plastics mainly involves adding a certain amount of antibacterial agent during the plastic granulation process. There are many types of antibacterial agents, including two main categories: inorganic and organic. Inorganic antibacterial agents include Ag, Zn-zeolite, Ag, and Zn-water-soluble glass, while organic antibacterial agents include quaternary ammonium salts, quaternary phosphine salts, imidazoles, pyridines, organometallic compounds, and so on. Both inorganic and organic antibacterial agents have their advantages and disadvantages. Inorganic antibacterial agents require large amounts and have poor compatibility with plastics; organic antibacterial agents have higher bactericidal efficiency and require smaller amounts, but they suffer from poor heat resistance, easy precipitation, and low safety.
[0004] Polybutylene adipate / terephthalate (PBAT) and polybutylene succinate / terephthalate (PBST) are flexible, biodegradable materials with good film blow molding properties, showing great promise for food packaging. However, their relatively poor stiffness limits their application in packaging films and bags.
[0005] Nano-modified antibacterial agents possess a long-lasting bactericidal mechanism, providing packaging materials with unique antibacterial properties. They can also act as reinforcing agents to enhance the overall application capabilities of PBAT and PBST in the packaging field. However, nano-antibacterial agents are prone to aggregation, making them difficult to disperse uniformly in biodegradable polyester matrices. Furthermore, their interfacial bonding with the resin matrix is poor, preventing them from maximizing their reinforcing function. Summary of the Invention
[0006] To address the aforementioned problems in the prior art, this invention proposes a composite antibacterial agent, a blown film and its preparation method and application, an antibacterial biodegradable polyester composition, a polyester material and its preparation method. The composite antibacterial agent provided by this invention comprises compatibilized binary copolymer microspheres loaded with antibacterial metal nanoparticles, exhibiting good compatibility with biodegradable resins. Furthermore, the N-vinylamide polymer in the composite antibacterial agent ensures that the biodegradable material containing the above-mentioned composite antibacterial agent maintains excellent antibacterial properties and high antibacterial efficiency throughout its entire life cycle, and in particular, does not migrate upon contact with water. When used in biodegradable materials, it can significantly improve the antibacterial and mechanical properties of the biodegradable materials, resulting in biodegradable materials possessing excellent mechanical properties, antibacterial properties, and biodegradability.
[0007] To achieve the above objectives, the present invention provides a composite antibacterial agent, characterized in that the composite antibacterial agent comprises maleic anhydride copolymer microspheres loaded with inorganic nanoparticles, a compound selected from at least one of long-chain aliphatic metal salts, long-chain aliphatic amides and long-chain aliphatic bases, an organometallic salt and an N-vinylamide polymer. Based on the total weight of the composite antibacterial agent, the content of the supported inorganic nanoparticle maleic anhydride copolymer microspheres is 80-92 wt%, the content of the organometallic salt is 0.1-8 wt%, the content of the compound is 0.1-4.5 wt%, and the content of the N-vinylamide polymer is 1-8 wt%. The particle size of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles is 1-2 μm.
[0008] A second aspect of the present invention provides a method for preparing the composite antibacterial agent described in the first aspect, characterized in that the preparation method includes the following steps: In the presence of a solvent, an organometallic salt, maleic anhydride copolymer microspheres, a compound selected from at least one of long-chain aliphatic metal salts, long-chain aliphatic amides, and long-chain aliphatic bases, and an N-vinylamide polymer are mixed and reacted, followed by solid-liquid separation to obtain the composite antibacterial agent.
[0009] A third aspect of the present invention provides the application of the composite antibacterial agent described in the first aspect in biodegradable plastics; The biodegradable plastic is selected from at least one of PBST, PBAT, PGA, PLA, PCL, PBSA, PBSL, PBS, PHA, and PPC.
[0010] A fourth aspect of the present invention provides an antibacterial biodegradable polyester composition, characterized in that the composition comprises a biodegradable copolyester, an antibacterial agent, and an antioxidant; The biodegradable copolyester has a melt index of 0.1-10 g / 10 min at 190 °C and a load of 2.16 kg; Based on 100 parts by weight of biodegradable copolyester, the amount of antibacterial agent is 0.05-5 parts by weight, and the amount of antioxidant is 0.05-5 parts by weight.
[0011] The antibacterial agent is the composite antibacterial agent described in the first aspect of this invention.
[0012] The fifth aspect of the present invention provides a method for preparing an antibacterial biodegradable polyester material, characterized in that the method includes: mixing an antibacterial biodegradable polyester composition and extruding and granulating it to obtain the antibacterial biodegradable polyester material; The antibacterial biodegradable polyester composition is the antibacterial biodegradable polyester composition described in the fourth aspect of this invention.
[0013] The sixth aspect of the present invention provides an antibacterial biodegradable polyester material prepared by the preparation method described in the fifth aspect of the present invention.
[0014] The seventh aspect of the present invention provides an antibacterial biodegradable polyester blown film, characterized in that the blown film is made from the antibacterial biodegradable polyester material provided in the sixth aspect of the present invention.
[0015] The eighth aspect of the present invention provides a method for preparing the antibacterial biodegradable polyester blown film according to the seventh aspect of the present invention, characterized in that the method includes: blow molding the antibacterial biodegradable polyester material provided in the fifth aspect to obtain the antibacterial biodegradable polyester blown film.
[0016] The ninth aspect of the present invention provides the application of the antibacterial biodegradable polyester blown film described in the eighth aspect of the present invention in antibacterial packaging film bags.
[0017] Through the above technical solutions, the composite antibacterial agent, blown film and its preparation method and application, antibacterial biodegradable polyester composition, polyester material and its preparation method provided by the present invention achieve the following beneficial effects: 1) The composite antibacterial agent provided by the present invention comprises compatibilized binary copolymer microspheres loaded with antibacterial metal nanoparticles, which have good compatibility with biodegradable resins. In addition, the N-vinylamide polymer in the composite antibacterial agent can ensure that the biodegradable material containing the above composite antibacterial agent has excellent antibacterial properties and high antibacterial efficiency throughout its entire life cycle. In particular, it does not migrate after contact with water. When used in biodegradable materials, it can significantly improve the antibacterial and mechanical properties of biodegradable materials, so that biodegradable materials have excellent mechanical properties, antibacterial properties and biodegradable properties.
[0018] 2) The biodegradable copolyester composition provided by the present invention uses biodegradable copolyester as the base resin and the composite antibacterial agent provided by the present invention as the antibacterial agent. The presence of the antibacterial agent can not only improve the antibacterial properties of the composition, but also significantly improve the opening properties of the composition. This makes the composition easy to process and has excellent opening properties when used to prepare blow molding. The blow molded film obtained has excellent mechanical properties, antibacterial properties and biodegradable properties.
[0019] 3) The antibacterial biodegradable polyester blown film provided by this invention has excellent mechanical and antibacterial properties, making it a superior material suitable for applications such as disposable medical supplies and disposable food packaging where antibacterial requirements are high. Furthermore, this blown film has a controllable degradation structure, allowing it to degrade through waste composting without causing secondary pollution, thus meeting the requirements of a circular economy.
[0020] 4) The method for preparing the antibacterial biodegradable polyester material and its blown film provided by the present invention is simple, effective and easy to operate. Detailed Implementation
[0021] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0022] The first aspect of the present invention provides a composite antibacterial agent, characterized in that the composite antibacterial agent comprises maleic anhydride copolymer microspheres loaded with inorganic nanoparticles, a compound selected from at least one of long-chain aliphatic metal salts, long-chain aliphatic amides and long-chain aliphatic bases, an organometallic salt and an N-vinylamide polymer. Based on the total weight of the composite antibacterial agent, the content of the supported inorganic nanoparticle maleic anhydride copolymer microspheres is 80-92 wt%, the content of the organometallic salt is 0.1-8 wt%, the content of the compound is 0.1-4.5 wt%, and the content of the N-vinylamide polymer is 1-8 wt%. The particle size of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles is 1-2 μm.
[0023] In this invention, the composite antibacterial agent comprises compatibilized binary copolymer microspheres loaded with antibacterial metal nanoparticles, which have good compatibility with biodegradable resins. In addition, the N-vinylamide polymer in the composite antibacterial agent can ensure that the biodegradable material containing the above-mentioned composite antibacterial agent has excellent antibacterial properties and high antibacterial efficiency throughout its entire life cycle. In particular, it does not migrate after contact with water. Furthermore, when the composite antibacterial agent is used in polyester compositions, it can not only improve the antibacterial properties of the composition, but also significantly improve the opening properties of the composition. This allows the composition to be used to prepare blow molds, which has simple processing, excellent opening properties, and the blown film produced has excellent mechanical properties, antibacterial properties, and biodegradable properties.
[0024] In this invention, by controlling the particle size of the loaded inorganic nanoparticle maleic anhydride copolymer microspheres and the content of each component in the composite antibacterial agent to meet the above-mentioned ranges, it is possible to ensure that the antibacterial agent is uniformly dispersed in the resin matrix, and to effectively reduce the amount of antibacterial agent added while ensuring antibacterial performance.
[0025] Furthermore, based on the total weight of the composite antibacterial agent, the content of the supported inorganic nanoparticle maleic anhydride copolymer microspheres is 82-91 wt%, the content of the organometallic salt is 1-7 wt%, the content of the compound is 2-4 wt%, and the content of the N-vinylamide polymer is 3-7 wt%. The particle size of the loaded inorganic nanoparticle maleic anhydride copolymer microspheres is 1.2-1.6 μm.
[0026] According to the present invention, the inorganic nanoparticles are selected from at least one of silver oxide, zinc oxide and cuprous oxide.
[0027] According to the present invention, based on the total weight of the loaded inorganic nanoparticle maleic anhydride copolymer microspheres, the content of the inorganic nanoparticles is 0.1-10 wt%, preferably 2-9 wt%.
[0028] In this invention, by controlling the loading amount of inorganic nanoparticles to meet the above-mentioned range, it is possible to ensure that the antibacterial agent is uniformly dispersed in the resin matrix, and to effectively reduce the amount of antibacterial agent added while ensuring antibacterial performance.
[0029] In a preferred embodiment of the present invention, the inorganic nanoparticles are selected from at least two of silver oxide, zinc oxide and cuprous oxide.
[0030] Specifically, the inorganic nanoparticles are selected from silver oxide and zinc oxide, wherein the weight ratio of silver oxide to zinc oxide is 0.5-6:1, preferably 1-3.5:1.
[0031] In this invention, the long-chain aliphatic metal salt is a C8-C20 aliphatic metal salt, for example, selected from at least one of disodium lauryl sulfosuccinate monoester, potassium monododecyl phosphate, potassium lauryl ether phosphate, and sodium lauryl amphoteric acetate; the long-chain aliphatic amide is selected from cocoyl diethanolamide and / or lauramidopropylamine oxide; the long-chain aliphatic base is selected from at least one of cocamidopropyl betaine, lauramidopropyl betaine, cocamidopropyl hydroxysulfonyl betaine, lauramidopropyl betaine, cocamidopropyl hydroxysulfonyl betaine, lauramidopropyl hydroxysulfonyl betaine, and fatty acid butter potassium soap.
[0032] According to the present invention, the N-vinylamide polymer is selected from N-vinylamide homopolymers and / or N-vinylamide copolymers.
[0033] In this invention, the N-vinylamide polymer is selected from N-vinylamide homopolymers or copolymers; the N-vinylamide homopolymer is a homopolymer selected from the following N-vinylamide monomers, and the N-vinylamide copolymer is a copolymer selected from any two or three of the following N-vinylamide monomers. Specifically, the N-vinylamide monomer is selected from N-vinylheptamide, N-vinyloctamide, N-vinylnonamide, N-vinyldecamide, N-methyl-N-vinylformamide, N-methyl-N-vinylacetamide, N-methyl-N-vinylpropamide, N-methyl-N-vinylbutamide, N-methyl-N-vinylpentamide, N-methyl-N-vinylhexamide, N-methyl-N-vinylheptamide, N-methyl-N-vinyloctamide, N-methyl-N-vinylnonamide, N-methyl-N-vinyldecamide, N-ethyl-N-vinylformamide, N-ethyl-N-vinylacetamide, N-ethyl-N-vinylpropamide, N-ethyl-N-vinylbutamide, N-ethyl-N-vinylpentamide, N-ethyl-N-vinylhexamide, N-ethyl-N-vinylheptamide, N-ethyl-N-vinyloctamide, N-ethyl-N-vinyldecamide, N-ethyl-N-vinylformamide, N-ethyl-N-vinylacetamide, N-ethyl-N-vinylpropamide, N-ethyl-N-vinylbutamide, N-ethyl-N-vinylpentamide, N-ethyl-N-vinylhexamide, N-ethyl-N-vinylheptamide, N-ethyl-N-vinyloctamide, and N-ethyl-N-vinylnonamide. N-Ethyl-N-vinyldecanoamide, N-n-propyl-N-vinylformamide, N-n-propyl-N-vinylacetamide, N-n-propyl-N-vinylpropanoamide, N-n-propyl-N-vinylbutanoamide, N-n-propyl-N-vinylpentanoamide, N-n-propyl-N-vinylhexanoamide, N-n-propyl-N-vinylheptanoamide, N-n-propyl-N-vinyloctanoamide, N-n-propyl-N-vinylnonanoamide, N-n-propyl-N-vinyl At least one of the following: decanoamide, N-isopropyl-N-vinylformamide, N-isopropyl-N-vinylacetamide, N-isopropyl-N-vinylpropionamide, N-isopropyl-N-vinylbutyramide, N-isopropyl-N-vinylpentanamide, N-isopropyl-N-vinylhexamide, N-isopropyl-N-vinylheptamide, N-isopropyl-N-vinyloctamide, N-isopropyl-N-vinylnonamide, and N-isopropyl-N-vinyldecanoamide.
[0034] In this invention, preferably, the N-vinylamide polymer is selected from at least one of poly(N-vinyldecanoamide-co-N-ethyl-N-vinyloctamide), poly(N-n-propyl-N-vinylnonamide), and poly(N-isopropyl-N-vinylheptamide).
[0035] In this invention, preferably, the relative molecular mass of the N-vinylamide polymer is less than or equal to 1000.
[0036] According to the present invention, the organometallic salt is selected from at least one of organosilver, organozinc and organocopper.
[0037] According to the present invention, the organic silver is selected from at least one of the following compounds: silver isooctanoate, silver nonanoate, silver decanoate, and silver heptanoate; preferably, silver isooctanoate.
[0038] According to the present invention, the organic zinc is selected from at least one of the following compounds: zinc acetate, zinc formate, zinc lactate, preferably zinc lactate.
[0039] According to the present invention, the organic copper is selected from at least one of the following compounds: copper isooctanoate, copper oxalate, copper succinate, copper glutarate, and copper adipate.
[0040] A second aspect of the present invention provides a method for preparing the composite antibacterial agent described in the first aspect of the present invention, characterized in that the preparation method includes the following steps: In the presence of a solvent, an organometallic salt, maleic anhydride copolymer microspheres, a compound selected from at least one of long-chain aliphatic metal salts, long-chain aliphatic amides, and long-chain aliphatic bases, and an N-vinylamide polymer are mixed and reacted, followed by solid-liquid separation to obtain the composite antibacterial agent.
[0041] The types of raw materials used in the second aspect of this invention are exactly the same as those described in the first aspect of this invention. To avoid repetition, the second aspect of this invention will not be described again, and those skilled in the art should not understand it as a limitation of this invention.
[0042] In this invention, the solvent can be a conventional solvent in the art, such as ethanol.
[0043] In this invention, according to the above preparation method, in the presence of a solvent and an N-vinylamide polymer, a compound selected from at least one of long-chain aliphatic metal salts, long-chain aliphatic amides, and long-chain aliphatic bases undergoes a co-precipitation reaction with an organometallic salt. The in-situ generated inorganic nanoparticles are loaded onto maleic anhydride copolymer microspheres to form a composite antibacterial agent containing maleic anhydride copolymer microspheres loaded with inorganic nanoparticles. The composite antibacterial agent prepared by this method has good compatibility with biodegradable resins. In addition, the N-vinylamide polymer in the composite antibacterial agent can ensure that the biodegradable material containing the above-mentioned composite antibacterial agent has excellent antibacterial properties and high antibacterial efficiency throughout its entire life cycle. In particular, it does not migrate after contact with water. Furthermore, when the composite antibacterial agent is used in polyester compositions, it can not only improve the antibacterial properties of the composition, but also significantly improve the opening properties of the composition. This allows the composition to be used to prepare blow molds, which has simple processing, excellent opening properties, and the blown film produced has excellent mechanical properties, antibacterial properties, and biodegradable properties.
[0044] According to the present invention, the amount of the organometallic salt is 0.1-5 parts by weight, the amount of the maleic anhydride copolymer microspheres is 0.05-5 parts by weight, the amount of the compound is 0.5-5 parts by weight, and the amount of the N-vinylamide polymer is 0.5-6 parts by weight.
[0045] In this invention, the organometallic salt is introduced in the form of an organometallic salt solution. There is no particular limitation on the type of solvent in the organometallic salt solution, as long as it can fully dissolve the organometallic salt and form a homogeneous solution.
[0046] In a preferred embodiment of the present invention, organosilver, organozinc, and organocopper are each added separately to a solvent, a mixture of a compound selected from at least one of long-chain aliphatic metal salts, long-chain aliphatic amides, and long-chain aliphatic bases, and an N-vinylamide polymer.
[0047] Further, the amount of the organometallic salt is 0.11-1 parts by weight, the amount of the maleic anhydride copolymer microspheres is 1.5-3.5 parts by weight, the amount of the compound is 1-2.5 parts by weight, and the amount of the N-vinylamide polymer is 1.5-4.5 parts by weight.
[0048] In one specific embodiment of the present invention, the preparation method of the composite antibacterial agent includes: At 70-90℃, the solvent, N-vinylamide polymer and at least one compound selected from long-chain aliphatic metal salts, long-chain aliphatic amides and long-chain aliphatic bases are mixed evenly. After adding organometallic salts and reacting for 25-50 min, maleic anhydride copolymer microspheres are added and the reaction is continued for 15-30 min. After separation and drying, the composite antibacterial agent is obtained.
[0049] In this invention, there are no particular limitations on the separation and drying methods and drying conditions; conventional separation and drying methods and drying conditions in the art can be used.
[0050] Maleic anhydride copolymer microspheres According to the present invention, the particle size of the maleic anhydride copolymer microspheres is 1000-1600 nm, preferably 1000-1500 nm.
[0051] According to the present invention, the copolymer in the maleic anhydride copolymer microspheres comprises structural unit A provided by maleic anhydride and structural unit B provided by α-methylstyrene. Based on the total molar amount of each structural unit in the copolymer, the molar content of structural unit A is 46-53% and the molar content of structural unit B is 47-54%.
[0052] Furthermore, the copolymer in the maleic anhydride copolymer microspheres comprises structural unit A provided by maleic anhydride and structural unit B provided by α-methylstyrene. Based on the total molar amount of each structural unit in the copolymer, the molar content of structural unit A is 46-53%, and the molar content of structural unit B is 47-54%.
[0053] Furthermore, based on the total molar amount of each structural unit in the copolymer, the molar content of structural unit A is 48-52%, and the molar content of structural unit B is 49-51%.
[0054] In this invention, the molar content of each structural unit in the copolymer is determined by... 1 The test was performed using H NMR, and the test method was as follows: 1 The ratio of the peak area corresponding to the characteristic hydrogen in the corresponding structural unit in H NMR is calculated.
[0055] In this invention, the maleic anhydride copolymer microspheres are prepared according to the following steps: S1. In an inert atmosphere, the monomers and initiators are dissolved in the reaction medium to form a homogeneous solution; S2. After the homogeneous solution undergoes a polymerization reaction to obtain a copolymer emulsion suspension, the maleic anhydride copolymer is obtained after solid-liquid separation. The polymerizing monomers are maleic anhydride and α-methylstyrene; based on the total weight of the polymerizing monomers, the amount of maleic anhydride is 29-63 wt%, and the amount of α-methylstyrene is 36-72 wt%. The reaction medium is a mixture of compound I shown in formula (1) and compound II shown in formula (2); Equation (1), Equation (2) R1 and R2 are each independently an alkyl group having 1 to 3 carbon atoms; R3, R4 and R5 are each independently H, methyl or ethyl.
[0056] In this invention, maleic anhydride and α-methylstyrene are copolymerized in a specific ratio in the presence of a specific reaction medium. The resulting maleic anhydride copolymer is a microsphere with excellent uniformity. The copolymer has a clean surface, good dispersibility in the medium, and does not aggregate. The resulting maleic anhydride copolymer has no special odor and has the characteristic of absorbing light of a certain wavelength and emitting light of a longer wavelength, thus it can be used as a photoluminescent material.
[0057] Furthermore, in order to obtain maleic anhydride copolymer microspheres with more uniform particle size and better morphology, the inventors studied the amount of maleic anhydride and α-methylstyrene used in the polymerization process. The study showed that when the amount of maleic anhydride was 40-50 wt% and the amount of α-methylstyrene was 45-55 wt% based on the total weight of the polymerizing monomers, the obtained maleic anhydride copolymer had more uniform particle size and better morphology, and the copolymer had better overall performance.
[0058] In this invention, based on the total weight of the homogeneous solution, the mass concentration of the polymeric monomer is 5-25 wt%, preferably 5-20 wt%.
[0059] In this invention, the initiator is an organic peroxide and / or an azo compound.
[0060] In this invention, the organic peroxide is selected from at least one of benzoyl peroxide, dicumyl peroxide, ditert-butyl peroxide, dodecyl peroxide, tert-butyl peroxide, diisopropyl peroxide, and dicyclohexyl peroxide.
[0061] In this invention, the azo compound is selected from azobisisobutyronitrile and / or azobisisoheptanenitrile.
[0062] In this invention, based on the total weight of the homogeneous solution, the mass concentration of the initiator is 0.2-3.1 wt%, preferably 1-2 wt%.
[0063] In this invention, a mixture of compound I shown in formula (1) and compound II shown in formula (2) is selected as the reaction medium. It can cooperate with the specific amounts of maleic anhydride and α-methylstyrene described in this invention to achieve a self-stabilizing precipitation polymerization reaction of maleic anhydride and α-methylstyrene. No stabilizer or co-stabilizer needs to be added to the polymerization reaction system. It has a self-stabilizing dispersion effect. The surface of the obtained polymer microspheres is clean and free from pollution. The obtained copolymer can be used as a photoluminescent material.
[0064] Furthermore, in formula (3), R1 and R2 are each independently methyl or ethyl.
[0065] Furthermore, in formula (3), R3, R4 and R5 are each independently methyl or ethyl.
[0066] In this invention, the amount of compound II used is 50-90 vol, based on the total volume of the reaction medium.
[0067] In this invention, when the amounts of compound I and compound II in the reaction medium meet the above-mentioned ranges, maleic anhydride copolymers with superior polymer microsphere morphology can be obtained. Furthermore, when the amount of compound II is 60-90 vol% based on the total volume of the reaction medium, the effect is even better.
[0068] In this invention, the conditions for the polymerization reaction include: a polymerization temperature of 60-90℃, preferably 70-80℃; and a polymerization time of 1-24h, preferably 3-12h.
[0069] In this invention, a water bath and / or an oil bath are used to provide the heat required for polymerization.
[0070] In this invention, the solid-liquid separation can be a conventional solid-liquid separation method in the art, such as centrifugal separation.
[0071] In this invention, when centrifugation is used, the centrifugation speed is 1000-4000 rad / min and the centrifugation time is 10-40 min.
[0072] According to the present invention, the conditions for the mixed reaction include: a reaction temperature of 70-90°C and a reaction time of 20-70 min.
[0073] The third aspect of this invention provides the application of the composite antibacterial agent described in the first aspect of this invention in biodegradable plastics; The biodegradable plastic is selected from at least one of PBST (polybutylene terephthalate), PBAT (polybutylene terephthalate), PGA (polyglycolic acid), PLA (polylactic acid), PCL (polycaprolactone), PBSA (polybutylene succinate), PBSL (polybutylene succinate-l-lactide), PBS (polybutylene succinate), PHA (polyhydroxyalkanoate), and PPC (polymethylethylene carbonate).
[0074] In this invention, the composite antibacterial agent described in the first aspect of the invention is used in biodegradable plastics. The composite antibacterial agent has good compatibility with biodegradable plastics, and the N-vinylamide polymer in the composite antibacterial agent can ensure that the biodegradable material containing the above-mentioned composite antibacterial agent has excellent antibacterial properties and high antibacterial efficiency throughout its entire life cycle. In particular, it does not migrate after contact with water; thus, the biodegradable plastic has excellent mechanical properties, antibacterial properties, and degradability.
[0075] A fourth aspect of the present invention provides an antibacterial biodegradable polyester composition, characterized in that the composition comprises a biodegradable copolyester, an antibacterial agent, and an antioxidant; The biodegradable copolyester has a melt index of 0.1-10 g / 10 min at 190 °C and a load of 2.16 kg; Based on 100 parts by weight of biodegradable copolyester, the amount of antibacterial agent is 0.05-5 parts by weight, and the amount of antioxidant is 0.05-5 parts by weight. The antibacterial agent is the composite antibacterial agent described in the first aspect of this invention.
[0076] In this invention, the composite antibacterial agent described in the first aspect of the invention is used in a biodegradable polyester composition. The presence of this antibacterial agent not only improves the antibacterial properties of the composition but also significantly improves its opening properties. In particular, the use of the composite antibacterial agent with the specific composition described above can also significantly improve the compatibility between inorganic nanoparticles and the biodegradable polyester matrix. In combination with antioxidants, this composition can be used to prepare blow molding molds, resulting in a simple process, excellent opening properties, and the blown film produced has excellent mechanical properties, anti-aging properties (weather resistance, mainly resistance to visible light and ultraviolet light), hydrolysis resistance, antibacterial properties, and biodegradability.
[0077] Furthermore, based on 100 parts by weight of the biodegradable copolyester, the amount of the antibacterial agent is 0.2-1 parts by weight; the amount of the antioxidant is 0.1-0.5 parts by weight.
[0078] In this invention, the biodegradable copolyester is an aliphatic aromatic copolyester.
[0079] According to the present invention, the melt index of the biodegradable copolyester at 190°C and 2.16 kg load is 0.1-10 g / 10 min, preferably 1-6 g / 10 min.
[0080] According to the present invention, the melt strength of the biodegradable copolyester is 0.05-0.5N, preferably 0.08-0.3N.
[0081] According to the present invention, the end carboxyl group content of the biodegradable copolyester is 2-20 mol%, preferably 6-16 mol%.
[0082] In this invention, there are no particular limitations on the source and preparation method of the biodegradable copolyester. It can be made in-house or purchased commercially, as long as at least one of the melt index, melt strength and carboxyl content of the biodegradable copolymer meets the requirements of this invention.
[0083] In this invention, the antioxidant can be any antioxidant conventionally used in the art. For example, the antioxidant is selected from 2,6-di-tert-butyl-4-methylphenol, 1,1,3-tris(2-methyl-4-hydroxy-5-tert-butylphenyl)butane, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-thiobis-[3-methyl-6-tert-butylphenol], 2,2'-thiobis-[4-methyl-6-tert-butylphenol], 1,3,5-di[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl]-hexahydrotriazine, tris(3,5-di-tert-butyl-4-hydroxybenzyl)-triisocyanate. Esters, N,N'-di(β-naphthyl)-p-phenylenediamine, N,N'-diphenyl-p-phenylenediamine, N-phenyl-N'-cyclohexyl-p-phenylenediamine, dilauryl thiodipropionate, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, triphenyl phosphite, trinonylphenyl phosphite, tris[2,4-di-tert-butylphenyl]phosphite, triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate], bis(2,4-dicumylphenyl)pentaerythritol-diphosphite, pentaerythritol dioctadecaphosphite, butylated hydroxytoluene (BHT), tert-butylhydroquinone (TBHQ), and antioxidant Chinox 20N, etc.
[0084] In a preferred embodiment of the present invention, the antioxidant is a mixture of hindered phenolic antioxidant and phosphite antioxidant in a mass ratio of 1:3 to 3:1.
[0085] In this invention, the hindered phenolic antioxidant is selected from antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; CAS No.: 6683-19-8), antioxidant 3114 (1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzyl)isocyanuric acid; CAS: 27676-62-6), antioxidant 245 (triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate]), and antioxidant 330 (1,3,5-trimethyl-2,4,6-tris(3,5-tert-butyl-4-hydroxybenzyl)benzene; CAS: At least one of 1709-70-2); the phosphite antioxidant is selected from at least one of antioxidant 168 (tris[2,4-di-tert-butylphenyl]phosphite; CAS: 31570-04-4), antioxidant 618 (pentaerythritol distearate diphosphite; CAS: 3806-34-6), bis(2,4-dicumylphenyl)pentaerythritol-diphosphite, pentaerythritol dioctadecyl diphosphite, and antioxidant 2,2'-ethylidene di(4,6-di-tert-butylphenyl)fluorophosphite, CAS: 118337-09-0.
[0086] According to the present invention, the antibacterial agent further includes a natural antibacterial agent, wherein the mass ratio of the natural antibacterial agent to the composite antibacterial agent is 0.1-10:1, preferably 0.4-2:1.
[0087] In this invention, the natural antibacterial agent and the composite antibacterial agent together constitute the antibacterial agent in the antibacterial biodegradable polyester composition described in the fourth aspect of this invention.
[0088] In this invention, the natural antibacterial agent can be selected from natural macromolecules such as chitosan, galangin, tea polyphenols, cinnamaldehyde, and eugenol. Among them, the effective antibacterial components of galangin include: cinnamyl alcohol, eugenol, aesculin, hyoscyamine, eugenol, α-guaiacol, β-apigenin, β-eudesmol, squalene, guaiacol, and thymol. Using the above-mentioned types of natural macromolecules as antibacterial agents not only improves the antibacterial properties of the composition but also acts as a plasticizer, improving the processing properties of the composition.
[0089] According to the present invention, the antibacterial biodegradable polyester composition may further include a slip agent, wherein the amount of the slip agent is 0.01-5 parts by weight, preferably 0.05-2 parts by weight, and more preferably 0.05-0.5 parts by weight, relative to 100 parts by weight of the biodegradable copolyester.
[0090] According to the present invention, the slip agent is selected from stearates and / or organic carboxylic acid amides, wherein the stearate may be selected from calcium stearate, etc., and the organic carboxylic acid amide may be selected from at least one of erucamide, oleamide, stearamide, stearic acid stearamide and N,N'-ethylene bis-stearamide, preferably N,N'-ethylene bis-stearamide.
[0091] According to the present invention, the antibacterial biodegradable polyester composition further includes a chain extender, wherein the amount of the chain extender is 0.01-5 parts by weight, preferably 0.05-2 parts by weight, and more preferably 0.1-1 parts by weight, relative to 100 parts by weight of the biodegradable copolyester.
[0092] According to the present invention, the chain extender is selected from at least one of styrene-glycidyl methacrylate copolymer, styrene-butyl acrylate-glycidyl methacrylate terpolymer, methylstyrene-methacrylate-glycidyl acrylate terpolymer, and styrene-methyl methacrylate-glycidyl methacrylate terpolymer.
[0093] According to the present invention, the antibacterial biodegradable polyester composition further includes a blending reinforcing component, wherein the amount of the blending reinforcing component is 2-20 parts by weight, preferably 4-12 parts by weight, and more preferably 5-10 parts by weight, relative to 100 parts by weight of the biodegradable copolyester.
[0094] In this invention, the blended reinforcing component is selected from at least one of polycaprolactone (PCL), polybutylene succinate (PBS), polyglycolic acid (PGA), polylactic acid (PLA), polyhydroxyalkanoate (PHA), and polymethyl ethylene carbonate (PPC), preferably selected from polylactic acid (PLA) and / or polyglycolic acid (PGA).
[0095] According to the present invention, the antibacterial biodegradable polyester composition further includes a crystallizing nucleating agent, wherein the amount of the crystallizing nucleating agent is 0.01-2 parts by weight, preferably 0.05-1 parts by weight, and more preferably 0.1-0.7 parts by weight, relative to 100 parts by weight of the biodegradable copolyester.
[0096] According to the present invention, the crystallizing nucleating agent is selected from at least one of hyperbranched polyamide, ethylene-methacrylate ionomer, diphenyl dihydrazide sebacate, diphenyl dihydrazide adipate, and zinc phenyl phosphate.
[0097] According to the present invention, the antibacterial biodegradable polyester composition further includes a dispersant, wherein the amount of the dispersant is 0.01-1 parts by weight, preferably 0.05-0.2 parts by weight, relative to 100 parts by weight of the biodegradable copolyester.
[0098] According to the present invention, the dispersant is selected from at least one of kaolin, mica, pyrope, clay, bauxite, titanium dioxide, basic magnesium carbonate, basic zinc carbonate, calcium carbonate, silicon dioxide, zinc borate and iron oxide, preferably kaolin.
[0099] According to the present invention, the antimicrobial biodegradable polyester composition further includes an anti-migration agent, wherein the amount of the anti-migration agent is 0.001-0.1 parts by weight, preferably 0.002-0.05 parts by weight, relative to 100 parts by weight of the biodegradable copolyester.
[0100] In this invention, adding the above-mentioned amount of anti-migration agent to the antibacterial biodegradable polyester composition can inhibit the precipitation of antibacterial agent in the antibacterial biodegradable polyester composition, thus ensuring the antibacterial properties of the polyester material or polyester film made from the composition.
[0101] According to the present invention, the anti-migration agent is selected from blocked polyisocyanates and / or fluorinated compounds.
[0102] According to the present invention, the fluorinated compound is selected from ethers of α-hydro-ω-hydroxy polyethylene oxide and α-fluoro-ω-(2-hydroxyethyl) poly(difluoromethylene), (C2H4O). n (CF2) nAt least one of C2H5FO, F(CF2CF2)3-8CH2CH2O(CH2CH2O)1-3H, F(CF2CF2)4O(CH2CH2O)6H, F(CF2CF2)3O(CH2CH2O)H, F(CF2CF2)O(CH2CH2O)8CH3 and F(CF2CF2)4CH2OCH2CH(OH)CH2O(CH2CH2O)4H.
[0103] In this invention, preferably, the etherified compound of α-hydro-ω-hydroxy polyoxyethylene and α-fluoro-ω-(2-hydroxyethyl) poly(difluoromethylene) is an etherified compound in which the molar ratio of α-hydro-ω-hydroxy polyoxyethylene to α-fluoro-ω-(2-hydroxyethyl) poly(difluoromethylene) is 1:1.
[0104] According to the present invention, the antibacterial biodegradable polyester composition further includes a hydrolysis inhibitor, wherein the amount of the hydrolysis inhibitor is 0.1-5 parts by weight, preferably 0.5-2 parts by weight, relative to 100 parts by weight of the biodegradable copolyester.
[0105] In this invention, adding an anti-hydrolysis inhibitor to the antibacterial biodegradable polyester composition can improve the hydrolysis resistance of the biodegradable film and extend the film's shelf life or service time.
[0106] According to the present invention, the hydrolysis inhibitor is selected from polycarbodiimide, monomeric carbodimethylamine, dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide, 2,2',6,6'-tetraisopropylcarbodimethylamine, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride. At least one of the following: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, 1-(3-dimethylaminopropyl)-3-ethyl-carbodiimide hydrochloride, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-(3-dimethylaminopropyl)-N'-ethyl-carbodiimide hydrochloride, and (3-dimethylaminopropyl)-3-ethylcarbodiamine.
[0107] The fifth aspect of the present invention provides a method for preparing an antibacterial biodegradable polyester material, characterized in that the method includes: mixing an antibacterial biodegradable polyester composition and extruding and granulating it to obtain the antibacterial biodegradable polyester material; The antibacterial biodegradable polyester composition is the antibacterial biodegradable polyester composition described in the fourth aspect of this invention.
[0108] In the fifth aspect of this invention, the raw materials for preparing the antibacterial biodegradable polyester material are the compositions described in the fourth aspect of this invention. Therefore, the types of raw materials in the fifth aspect of this invention are exactly the same as those described in the fourth aspect of this invention. To avoid repetition, this invention will not be described again in this second aspect, and those skilled in the art should not understand it as a limitation of this invention.
[0109] In this invention, mixing and extruding the composition containing the composite antibacterial agent provided in the fourth aspect of this invention can improve both the opening properties and antibacterial properties of the resulting polyester material.
[0110] According to the present invention, the conditions for extrusion granulation include: an extrusion temperature of 140-230°C, preferably 150-180°C; and a screw speed of 100-500 rpm, preferably 150-250 rpm.
[0111] In one specific embodiment of the present invention, the composition contains a blended reinforcing component, and when the blended reinforcing component contains polyglycolic acid, such as homopolymer polyglycolic acid, the extrusion granulation conditions include: an extrusion temperature of 230°C and a screw speed of 150-250 rpm.
[0112] In this invention, the extrusion granulation can be carried out in conventional equipment in the art, such as a twin-screw extruder.
[0113] In this invention, the extrusion temperature refers to the extrusion temperature set in the extrusion equipment, such as a twin-screw extruder.
[0114] In one specific embodiment of the present invention, the method for preparing the antibacterial biodegradable polyester material includes: (a) The biodegradable copolyester is mixed with an antioxidant and granulated to obtain a premix; (b) The premix, composite antibacterial agent, optional slip agent, optional chain extender, optional blending reinforcing component, optional crystallizing nucleating agent, optional dispersant, optional anti-migration agent and optional hydrolysis inhibitor are extruded and granulated to obtain the antibacterial biodegradable polyester material, wherein the biodegradable copolyester, antioxidant, composite antibacterial agent, optional slip agent, optional chain extender, optional blending reinforcing component, optional crystallizing nucleating agent, optional dispersant, optional anti-migration agent and optional hydrolysis inhibitor constitute the antibacterial biodegradable polyester composition provided in the fourth aspect of the present invention.
[0115] The sixth aspect of the present invention provides an antibacterial biodegradable polyester material prepared by the preparation method described in the fifth aspect of the present invention.
[0116] The seventh aspect of the present invention provides an antibacterial biodegradable polyester blown film, characterized in that the blown film is made from the antibacterial biodegradable polyester material provided in the sixth aspect of the present invention.
[0117] In this invention, the antibacterial biodegradable polyester blown film possesses excellent mechanical and antibacterial properties, making it a superior material suitable for applications such as disposable medical supplies and disposable food packaging where antibacterial requirements are high. Furthermore, this blown film has a controllable degradation structure, allowing it to degrade through waste composting without causing secondary pollution, thus meeting the requirements of a circular economy.
[0118] According to the present invention, the thickness of the antibacterial biodegradable polyester blown film can be adjusted according to requirements and specific processes. Preferably, the thickness of the antibacterial biodegradable polyester blown film can be 5-100 μm, and more preferably 10-20 μm.
[0119] According to the present invention, the tensile breaking stress of the antibacterial biodegradable polyester blown film is greater than or equal to 18 MPa, preferably greater than or equal to 25 MPa, for example, it can be 25-100 MPa.
[0120] According to the present invention, the longitudinal tensile strength of the antibacterial biodegradable polyester blown film is greater than or equal to 18 MPa, and the transverse tensile strength is greater than or equal to 16 MPa; preferably, the longitudinal tensile strength is greater than or equal to 24 MPa, and the transverse tensile strength is greater than or equal to 20 MPa.
[0121] According to the present invention, the longitudinal elongation at break of the antibacterial biodegradable polyester blown film is greater than or equal to 250%, and the transverse elongation at break is greater than or equal to 300%; preferably, the longitudinal elongation at break is greater than or equal to 300%, and the transverse elongation at break is greater than or equal to 350%.
[0122] According to the present invention, the light transmittance of the antibacterial biodegradable polyester blown film is greater than or equal to 89%, preferably greater than or equal to 90%.
[0123] The eighth aspect of the present invention provides a method for preparing the antibacterial biodegradable polyester blown film according to the seventh aspect of the present invention, characterized in that the method includes: blow molding the antibacterial biodegradable polyester material provided in the fifth aspect to obtain the antibacterial biodegradable polyester blown film.
[0124] According to the present invention, the conditions for blow molding include: a blown film temperature of 150-210°C, preferably 1600-200°C.
[0125] In this invention, the blown film temperature refers to the film outlet temperature of the blown film equipment, such as a blown film machine. In this invention, the blown film machine can be a conventional blown film machine in the art, such as a bottom-blowing water-cooled blown film machine, a flat-blowing air-cooled blown film machine, or a traditional top-blowing air-cooled biodegradable copolyester blown film unit.
[0126] According to the present invention, the blow-molding ratio is 1.5-3:1, preferably 2-2.5:1.
[0127] In one specific embodiment of the present invention, the antibacterial biodegradable polyester blown film is prepared according to the following steps: I) The biodegradable copolyester is mixed with an antioxidant and granulated to obtain a premix; II) Mix the compound antibacterial agent with the natural antibacterial agent to obtain an antibacterial agent mixture; III) The premix and the antibacterial agent mixture are mixed, and slip agent, chain extender, blending reinforcement component, crystallizing nucleating agent, dispersant, anti-migration agent and hydrolysis inhibitor are added. The mixture is then extruded and granulated to obtain antibacterial biodegradable polyester material. IV) The antibacterial biodegradable polyester material is blown into a film to obtain the antibacterial biodegradable polyester blown film.
[0128] The ninth aspect of the present invention provides the application of the antibacterial biodegradable polyester blown film described in the eighth aspect of the present invention in antibacterial packaging film bags.
[0129] The present invention will be described in detail below through embodiments. In the following embodiments, Polylactic acid (PLA), Corbian, LX175; Polyglycolic acid (PGA), Pujing Chemical; Anti-migration agent K1: an etherification of α-hydro-ω-hydroxy polyethylene oxide and α-fluoro-ω-(2-hydroxyethyl)poly(difluoromethylene) (1:1); Anti-migration agent K2: (C2H4O) n (CF2) n C2H5FO; Anti-migration agent K3: F(CF2CF2)O(CH2CH2O)8CH3; Anti-migration agent K4: F(CF2CF2)4O(CH2CH2O)6H; Anti-migration agent K5: F(CF2CF2)4CH2OCH2CH(OH)CH2O(CH2CH2O)4H; Anti-migration agent K6:F(CF2CF2)3-8CH2CH2O(CH2CH2O)1-3H; Anti-migration agent K7: F(CF2CF2)3O(CH2CH2O)H; Chain extender N1: styrene-glycidyl methacrylate copolymer; Chain extender N2: styrene-butyl acrylate-glycidyl methacrylate terpolymer; Chain extender N3: styrene-methyl methacrylate-glycidyl methacrylate terpolymer; Crystallization nucleating agent C1: diphenyl dihydrazide sebacate; Crystallization nucleating agent C2: diphenyldihydrazide adipic acid; Crystallization nucleating agent C3: Zinc phenyl phosphate; Crystallization nucleating agent C4: ethylene-methacrylic acid ionomer, Dow Chemical Company; Hydrolysis inhibitor S1: 2,2',6,6'-tetraisopropyldiphenylcarbodiimide; Hydrolysis inhibitor S2: 1-(3-dimethylaminopropyl)-3-ethyl-carbodiimide hydrochloride; Hydrolysis inhibitor S3: 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride; Hydrolysis inhibitor S4: 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride; Hydrolysis inhibitor S5: N-(3-dimethylaminopropyl)-N'-ethyl-carbodiimide hydrochloride; Hydrolysis inhibitor S6: (3-dimethylaminopropyl)-3-ethylcarbodiamine; Hydrolysis inhibitor S7: N,N'-diisopropylcarbodiimide; Hydrolysis inhibitor S8: dicyclohexylcarbodiimide; Hydrolysis inhibitor S9: 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride; Hydrolysis inhibitor S10: polycarbodiimide; Slip agent B1: Oleamide; Slip agent B2: Erucamide; Slip agent B3: N,N'-ethylene bis-stearamide; Slip agent B4: stearamide; The types, sources, melt flow rate (MFR), melt strength, and carboxyl content of biodegradable copolymers are shown in Table 1. Drop impact: Tested according to the method described in ASTM D1709 Method A; Mechanical properties: GB / T1040.3 Determination of tensile properties of plastics - Part III; Opening performance: GB / T 10006-2021 Determination of the coefficient of friction of plastic films and sheets. The coefficient of friction reflects the amount of external force required for two layers of film to slide against each other, and can reflect the quality of the film's opening performance. Antibacterial properties: GB / T 31402-2015 Test method for antibacterial properties of plastic surfaces, test bacteria: Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538; Light transmittance: Tested according to the method specified in GB / T 2410-2008; Haze: Tested according to the method specified in GB / T 2410-2008; Water vapor transmission rate: conducted according to GB / T 1037, with test conditions of 38℃±0.6℃ and relative humidity of 90%±2%. Melt index: Tested according to GB / T 3682.1-2018, with test conditions of 190℃ and 2.16kg; Melt strength: Single screw extruder die diameter 2mm, test temperature 170℃, stretching roll gap 0.4mm, test equipment: melt tensile rheometer, GOTTFERT GmbH, Germany, model Rheotens 71.97.
[0130] The end carboxyl group content of biodegradable copolyesters shall be determined according to Method A in GB / T 14190-2017 5.4. The content of inorganic nanoparticles in maleic anhydride copolymer microspheres loaded with inorganic nanoparticles was determined by TGA. The test method was as follows: under nitrogen conditions, the composite antibacterial agent was heated from 23℃ to 800℃ at a rate of 10℃ / min to obtain the ash content, which was the content of inorganic nanoparticles. The particle size of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles was measured by SEM. The content of at least one compound selected from long-chain aliphatic metal salts, long-chain aliphatic amides, and long-chain aliphatic bases, and the N-vinylamide polymer in the compound antibacterial agent is determined by... 13 The mole fraction was obtained by quantitative measurement using C mass NMR spectroscopy, and the mass fraction was calculated from the result. The content of organometallic salts in compound antibacterial agents is determined by... 13 Measured by C mass nuclear magnetic resonance spectroscopy; Unless otherwise specified, all raw materials used in the embodiments and comparative examples of this invention are commercially available products.
[0131] Table 1
[0132] Preparation Example This preparation example illustrates the preparation of a compound antibacterial agent.
[0133] KJWQ401 (i) 5 g maleic anhydride, 0.9 g azobisisobutyronitrile, 6 g α-methylstyrene, 40 ml acetone, and 60 ml toluene were added to a 500 mL three-necked flask. After the materials were mixed evenly, a homogeneous solution was obtained. Nitrogen gas was purged for 20 minutes, and the three-necked flask was transferred to a 70 °C water bath and reacted for 5 h. After the reaction was completed, the resulting polymer emulsion suspension was centrifuged at 1000 rad / min for 40 minutes to obtain 7.8 g of polymer A1, corresponding to a polymer yield of 71%. The size of the polymer microspheres A1 was 1200 nm. The concentration of the monomer was 11.5 wt% and the concentration of the initiator was 0.9 wt% based on the total weight of the homogeneous solution.
[0134] The polymer microspheres A1 were subjected to 1H NMR analysis. Based on the total molar amount of each structural unit in the polymer, the molar content of structural unit A provided by maleic anhydride was 46%, and the molar content of structural unit B provided by α-methylstyrene was 54%.
[0135] (ii) 85 mL of anhydrous ethanol was added to a 250 mL round-bottom flask and heated to 75 °C in an oil bath. Then, 1.5 g of disodium lauryl sulfosuccinate monoester (a long-chain aliphatic metal salt, compound) and 2 g of poly(N-vinyldecylamide-co-N-ethyl-N-vinyloctamide) (N-vinylamide polymer) were added to the reaction vessel. After both reacted completely and dissolved, 1 mL of 0.5 mol / L zinc lactate solution (organic zinc) was added, and the reaction time was started. After 10 min of reaction, 10 mL of 0.05 mol / L silver isooctanoate solution (organic silver) was added. After mechanical stirring for 25 min (this process forms silver oxide and zinc oxide nanoparticles), 2 g of the above polymer microspheres A1 were added, and stirring was continued for 20 min. After centrifugation, the mixture was spray-dried to obtain the composite antibacterial agent KJWQ401. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0136] KJWQ402 (i) 9.8 g maleic anhydride, 0.9 g azobisisobutyronitrile, 12 g α-methylstyrene, 40 ml acetone, and 60 ml o-xylene were added to a 500 mL three-necked flask. After the materials were mixed evenly, a homogeneous solution was obtained. Nitrogen gas was purged for 20 minutes, and the three-necked flask was placed in a 60 °C water bath for 24 h. After the reaction was completed, the resulting polymer emulsion suspension was centrifuged at 2000 rad / min for 20 minutes to obtain 16.8 g of polymer A2, corresponding to a polymer yield of 77%. The size of polymer microspheres A2 was 1600 nm. The concentration of the monomer was 20.4 wt% and the concentration of the initiator was 0.8 wt% based on the total weight of the homogeneous solution.
[0137] The polymer microspheres A2 were subjected to 1H NMR analysis to determine the total molar content of each structural unit in the polymer. The molar content of structural unit A provided by maleic anhydride was 50%, and the molar content of structural unit B provided by α-methylstyrene was 50%.
[0138] (ii) Add 90 mL of anhydrous ethanol to a 250 mL round-bottom flask and heat in an oil bath to 80 °C. Then add 2 g of potassium monododecyl phosphate (compound) and 4 g of poly(N-n-propyl-N-vinylnonamide) (N-vinylamide polymer) to the reaction vessel. After both react completely and dissolve, add 0.5 mL of 0.2 mol / L copper oxalate solution (organic copper) and start timing. After reacting for 15 min, add 40 mL of 0.02 mol / L silver decanoate solution (organic silver) and stir mechanically for 10 min. Then add 2 g of the above polymer microspheres A2 and continue stirring for 20 min. After centrifugation, spray dry to obtain the composite antibacterial agent KJWQ402. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0139] KJWQ403 (i) 9.6 g maleic anhydride, 0.69 g azobisisobutyronitrile, 4.72 g α-methylstyrene, 6.24 g styrene, and 86.8 g isoamyl acetate were added to a 500 mL three-necked flask. After the materials were mixed evenly, nitrogen gas was purged for 20 minutes. The three-necked flask was then placed in a 75 °C water bath and reacted for 3 hours. After the reaction was completed, the resulting polymer emulsion suspension was centrifuged at 2000 rad / min for 20 minutes to obtain 16.65 g of polymer solid A3, corresponding to a polymer yield of 75%. The particle size of polymer microspheres A3 was 1400 nm.
[0140] The polymer microspheres A3 were subjected to 1H NMR analysis. Based on the total molar amount of each structural unit in the polymer, the molar content of maleic anhydride structural unit was 51%, the molar content of styrene structural unit was 27%, and the molar content of α-methylstyrene structural unit was 22%.
[0141] (ii) Add 80 mL of anhydrous ethanol to a 250 mL round-bottom flask, heat in an oil bath to 80 °C and maintain the temperature. Then add 2 g of potassium monododecyl phosphate and 2 g of poly(N-isopropyl-N-vinylheptamide) to the reaction vessel, allowing them to react fully and dissolve completely. Add 0.5 mL of 0.2 mol / L zinc formate solution and start timing. After reacting for 15 min, add 40 mL of 0.02 mol / L silver decanoate solution and stir mechanically for 15 min. Then add 2 g of polymer microspheres A3 and continue stirring for 20 min. Centrifuge and spray dry to obtain the composite antibacterial agent KJWQ403. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0142] KJWQ404 (i) 4.9 g maleic anhydride, 0.2 g azobisisobutyronitrile, 5.9 g α-methylstyrene, 40 ml acetone, and 60 ml benzene were added to a 500 mL three-necked flask. After the materials were mixed evenly, a homogeneous solution was obtained. Nitrogen gas was purged for 20 minutes, and the three-necked flask was transferred to an 80 °C water bath and reacted for 12 h. After the reaction was completed, the resulting polymer emulsion suspension was centrifuged at 2000 rad / min for 20 minutes to obtain 7.8 g of polymer solid, corresponding to a polymer yield of 72%. The size of the polymer microspheres A4 was 1080 nm. The concentration of the monomer was 16.8 wt% and the concentration of the initiator was 0.2 wt% based on the total weight of the homogeneous solution.
[0143] The polymer microspheres A4 were subjected to 1H NMR analysis. Based on the total molar amount of each structural unit in the polymer, the molar content of structural unit A provided by maleic anhydride was 48%, and the molar content of structural unit B provided by α-methylstyrene was 52%.
[0144] (ii) 100 mL of anhydrous ethanol was added to a 250 mL round-bottom flask and heated to 70 °C in an oil bath. Then, 2 g of fatty acid potassium tallow soap (CAS No.: 68002-80-2) and 2 g of poly(N-vinyldecanoamide-co-N-ethyl-N-vinyloctanoamide) were added to the reaction vessel. After both reacted completely and dissolved, 0.5 mL of 0.2 mol / L zinc lactate solution was added, and the reaction time was started. After 20 min of reaction, 30 mL of 0.03 mol / L silver isooctanoate solution was added, and the mixture was mechanically stirred for 25 min. Then, 3 g of polymer microspheres A4 were added, and the mixture was stirred for another 20 min. After centrifugation, the mixture was spray-dried to obtain the composite antibacterial agent KJWQ404. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0145] KJWQ405 4.9 g of maleic anhydride, 0.9 g of azobisisobutyronitrile, 6 g of α-methylstyrene, 40 ml of acetone, and 60 ml of toluene were added to a 500 mL three-necked flask. After thorough mixing, nitrogen gas was purged for 20 minutes. The flask was then placed in an 80 °C water bath and reacted for 24 h. After the reaction was complete, the resulting polymer emulsion suspension was centrifuged at 2000 rad / min for 20 minutes to obtain 8.3 g of polymer solid, corresponding to a polymer yield of 76%. The polymer microspheres had a size of 1200 nm. The concentration of the monomer was 6.3 wt%, and the concentration of the initiator was 1.1 wt%, based on the total weight of the homogeneous solution.
[0146] The polymer microspheres A5 were subjected to 1H NMR analysis. Based on the total molar amount of each structural unit in the polymer, the molar content of structural unit A provided by maleic anhydride was 53%, and the molar content of structural unit B provided by α-methylstyrene was 47%.
[0147] (ii) 100 mL of anhydrous ethanol was added to a 250 mL round-bottom flask and heated to 70 °C in an oil bath. Then, 2 g of cocamidopropyl betaine (cocamidopropyl dimethylamine acetone) and 2 g of poly(N-n-propyl-N-vinylnonamide) were added to the reaction vessel. After both reacted completely and dissolved, 0.4 mL of 0.1 mol / L zinc lactate solution was added, and the reaction was started. After 20 min of reaction, 30 mL of 0.02 mol / L copper isooctanoate solution was added, and the mixture was mechanically stirred for 15 min. Then, 2 g of the above polymer microspheres were added, and the mixture was stirred for another 20 min. After centrifugation, the mixture was spray-dried to obtain the composite antibacterial agent KJWQ405. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0148] KJWQ406 The method of KJWQ401 was followed, with the difference that the amounts of organic zinc and organic silver were different in step (ii). Specifically, 0.5 mL of 0.5 mol / L zinc lactate solution and 20 mL of 0.05 mol / L silver isooctanoate solution were added. The composite antibacterial agent KJWQ406 was obtained. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0149] KJWQ407 The method of KJWQ401 was followed, with the difference that the amounts of organic zinc and organic silver were different in step (ii). Specifically, 0.3 mL of 0.5 mol / L zinc lactate solution and 15 mL of 0.05 mol / L silver isooctanoate solution were added. The composite antibacterial agent KJWQ407 was obtained. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0150] KJWQ408 The method was followed according to KJWQ401, except that in step (ii), 10 mL of 0.05 mol / L silver decanoate was used instead of 10 mL of 0.05 mol / L silver isooctanoate. The composite antibacterial agent KJWQ408 was obtained. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0151] KJWQ409 Prepared according to the method of KJWQ401, with the following difference: In step (ii), 85 mL of anhydrous ethanol was added to a 250 mL round-bottom flask, heated to 40 °C in an oil bath, and then 1.5 g of disodium lauryl sulfosuccinate monoester (long-chain aliphatic metal salt, compound) and 2 g of poly(N-vinyldecanoamide-co-N-ethyl-N-vinyloctanoamide) (N-vinylamide polymer) were added to the reaction vessel. After both reacted fully and dissolved completely, 1 mL of 0.5 mol / L zinc lactate solution (organic zinc) was added, and timing was started. After reacting for 40 min, 10 mL of 0.05 mol / L silver isooctanoate solution (organic silver) was added. After mechanical stirring for 60 min (this process forms silver oxide and zinc oxide nanoparticles), 2 g of the above polymer microspheres A1 were added. After stirring for another 30 min, the mixture was centrifuged and spray-dried to obtain the composite antibacterial agent KJWQ409. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0152] KJWQ410 Prepared according to the method of KJWQ401, except that in step (ii), silver isooctanoate is not added, unlike in KJWQ401. The composite antibacterial agent KJWQ410 is obtained. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0153] KJWQ411 Prepared according to the method of KJWQ401, except that in step (ii), zinc lactate is not added, unlike in KJWQ401. The composite antibacterial agent KJWQ411 is obtained. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0154] KJWQD101 2.6 g of maleic anhydride, 1 g of azobisisobutyronitrile, 3 g of α-methylstyrene, 40 ml of acetone, and 60 ml of p-xylene were added to a 500 mL three-necked flask. After thorough mixing, a homogeneous solution was obtained. Nitrogen gas was purged for 20 minutes, and the flask was then placed in a 90 °C water bath for 2 hours. After the reaction was complete, the resulting polymer emulsion suspension was centrifuged at 4000 rad / min for 10 minutes to obtain 4.2 g of polymer D1, corresponding to a polymer yield of 75%. The size of the polymer microspheres D1 was 500 nm. The concentration of the monomer was 6.3 wt% and the concentration of the initiator was 1.1 wt% based on the total weight of the homogeneous solution.
[0155] The polymer microspheres D1 were subjected to 1H NMR analysis. Based on the total molar amount of each structural unit in the polymer, the molar content of structural unit A provided by maleic anhydride was 47%, and the molar content of structural unit B provided by α-methylstyrene was 53%.
[0156] 90 mL of anhydrous ethanol was added to a 250 mL round-bottom flask and heated to 80 °C in an oil bath. Then, 2 g of sodium lauryl amphoteric acetate and 2 g of N-ethyl-N-vinylpropionamide were added to the reaction vessel. After both reacted completely and dissolved, 1 mL of 0.3 mol / L zinc acetate solution was added, and the reaction time was started. After 10 min, 15 mL of 0.03 mol / L silver nonanoate solution was added, and the mixture was mechanically stirred for 30 min. Then, 1.5 g of the polymer microspheres were added, and the mixture was stirred for another 20 min. After centrifugation, the mixture was spray-dried to obtain the composite antibacterial agent KJWQD101. The composition of the composite antibacterial agent is shown in Table 2, and the parameters of the maleic anhydride copolymer microspheres loaded with inorganic nanoparticles in the composite antibacterial agent are shown in Table 3.
[0157] Table 2
[0158] Microspheres refer to maleic anhydride copolymer microspheres loaded with inorganic nanoparticles. Table 3
[0159] Microspheres refer to maleic anhydride copolymer microspheres loaded with inorganic nanoparticles. Examples 1-12 The examples illustrate the method for preparing antibacterial and biodegradable polyester films: I) The copolyester in Table 1 is mixed with antioxidant 1010 and antioxidant 168 in a twin-screw extruder at 170°C and granulated to obtain a premix; II) The composite antibacterial agent prepared in the preparation example is mixed with a natural antibacterial agent to obtain an antibacterial agent mixture; III) The premix, antibacterial agent mixture, slip agent, chain extender, blended reinforcing component, crystallizing nucleating agent, dispersant, anti-migration agent and hydrolysis inhibitor are extruded and granulated in a twin-screw extruder at 170°C to obtain antibacterial biodegradable polyester material; IV) The antibacterial biodegradable polyester material was blown into a film on a blown film machine. Under certain die temperature and blow-up ratio, a film with a thickness of 20±0.5µm was obtained.
[0160] The types and proportions of each raw material are shown in Table 4; the blown film die temperature and blow-up ratio are shown in Table 5. The antioxidant dosage is fixed at 1010:168=1:2, with 100 parts of copolyester, 0.1 parts of 1010, and 0.2 parts of 168.
[0161] The prepared film was subjected to performance tests. The results of its optical and barrier properties are shown in Table 6, and its antibacterial, opening, mechanical and other properties are shown in Table 7.
[0162] Examples 13-19 Thin films were prepared according to the method of Example 1, except that KJWQ405-KJWQ411 were used instead of KJWQ401.
[0163] The prepared film was subjected to performance tests. The results of its optical and barrier properties are shown in Table 6, and its antibacterial, opening, mechanical and other properties are shown in Table 7.
[0164] Comparative Examples 1-5 Thin films were prepared according to the method of Example 1, except that the types and amounts of each component were different from those in Example 1, as detailed in Table 4; the blown film die temperature and blow-up ratio are shown in Table 5.
[0165] The prepared films were subjected to performance tests. The results of their optical and barrier properties are shown in Table 6, and their antibacterial, opening, and mechanical properties are shown in Table 7.
[0166] Comparative Example 6 The prepared film was subjected to performance tests. The results of its optical and barrier properties are shown in Table 6, and its antibacterial, opening, and mechanical properties are shown in Table 7.
[0167] Comparative Example 7 Except for the absence of an anti-migration agent, the prepared film was subjected to performance tests in the same manner as in Example 2. The results of its optical and barrier properties are shown in Table 6, and its antibacterial, opening, and mechanical properties are shown in Table 7.
[0168] Comparative Example 8 Except for the absence of hydrolysis inhibitors, the prepared films were subjected to performance tests in the same manner as in Example 2. The results of the optical and barrier properties tests are shown in Table 6, and the antibacterial, opening, and mechanical properties are shown in Table 7.
[0169] Table 4 (parts by weight)
[0170] Table 4 (continued) (parts by weight)
[0171] Table 5
[0172] Table 6
[0173] Table 7
[0174] As can be seen from the data in Tables 6 and 7, when the composite antibacterial agent containing maleic anhydride copolymer microspheres loaded with inorganic antibacterial nanoparticles provided by the present invention is added to the biodegradable copolyester, the resulting film has excellent opening performance, antibacterial performance and better mechanical properties when blown into a film.
[0175] Furthermore, in Examples 6 and 7, when the natural antibacterial agent is compounded with the composite antibacterial agent of the present invention, the antibacterial effect of the film can be further improved.
[0176] As can be seen from Example 1 and Comparative Example 6, natural antibacterial agents such as chitosan are low-molecular-weight compounds, and excessive addition to the system will affect the mechanical properties of the blown biodegradable film. As can be seen from Comparative Examples 1-4, antibacterial agents without added copolymer microspheres as a carrier cannot be well combined with and uniformly dispersed in the biodegradable resin matrix, resulting in lower mechanical strength and antibacterial effect.
[0177] In Comparative Examples 1-4, since the composite antibacterial agent provided by the present invention was not added, the compatibility and adhesion of the antibacterial agent with the biodegradable copolyester were generally low, resulting in a significant decrease in the antibacterial properties of the film over time.
[0178] In Comparative Example 7, the lack of an anti-migration agent led to a significant decrease in the antibacterial properties of the film over time. Specifically, after 3 months, the antibacterial rate of the film prepared in Comparative Example 7 decreased to 96.3% and 95.9% against Escherichia coli and Staphylococcus aureus, respectively.
[0179] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A composite antibacterial agent, characterized in that, The composite antibacterial agent comprises maleic anhydride copolymer microspheres loaded with antibacterial inorganic nanoparticles, a compound selected from at least one of long-chain aliphatic metal salts, long-chain aliphatic amides and long-chain aliphatic bases, an organometallic salt and an N-vinylamide polymer. Based on the total weight of the composite antibacterial agent, the content of the maleic anhydride copolymer microspheres loaded with antibacterial inorganic nanoparticles is 80-92 wt%, the content of the organometallic salt is 0.1-8 wt%, the content of the compound is 0.1-4.5 wt%, and the content of the N-vinylamide polymer is 1-8 wt%. The particle size of the maleic anhydride copolymer microspheres loaded with antibacterial inorganic nanoparticles is 1-2 μm; The copolymer in the maleic anhydride copolymer microspheres comprises structural unit A provided by maleic anhydride and structural unit B provided by α-methylstyrene. Based on the total molar amount of each structural unit in the copolymer, the molar content of structural unit A is 46-53% and the molar content of structural unit B is 47-54%.
2. The composite antibacterial agent according to claim 1, wherein, Based on the total weight of the composite antibacterial agent, the content of the maleic anhydride copolymer microspheres loaded with antibacterial inorganic nanoparticles is 82-91 wt%, the content of the organometallic salt is 1-7 wt%, the content of the compound is 2-4 wt%, and the content of the N-vinylamide polymer is 3-7 wt%. The particle size of the loaded antibacterial inorganic nanoparticle maleic anhydride copolymer microspheres is 1.2-1.6 μm.
3. The composite antibacterial agent according to claim 1 or 2, wherein, The antibacterial inorganic nanoparticles are selected from at least one of silver oxide, zinc oxide and cuprous oxide; And / or, based on the total weight of the maleic anhydride copolymer microspheres loaded with antibacterial inorganic nanoparticles, the content of the inorganic nanoparticles is 0.1-10 wt%; And / or, the N-vinylamide polymer is selected from N-vinylamide homopolymers and / or N-vinylamide copolymers; And / or, the organometallic salt is selected from at least one of organosilver, organozinc and organocopper.
4. The composite antibacterial agent according to claim 3, wherein, Based on the total weight of the maleic anhydride copolymer microspheres loaded with antibacterial inorganic nanoparticles, the content of the antibacterial inorganic nanoparticles is 2-9 wt%. And / or, the organic silver is selected from at least one of the following compounds: silver isooctanoate, silver nonanoate, silver decanoate, and silver heptanoate; And / or, the organic zinc is selected from at least one of the following compounds: zinc acetate, zinc formate, zinc lactate; And / or, the organic copper is selected from at least one of the following compounds: copper isooctanoate, copper oxalate, copper succinate, copper glutarate, and copper adipate.
5. The composite antibacterial agent according to claim 4, wherein, The organic silver is silver isooctanoate; And / or, the organic zinc is zinc lactate.
6. A method for preparing the composite antibacterial agent according to any one of claims 1-5, characterized in that, The preparation method includes the following steps: In the presence of a solvent, an organometallic salt, maleic anhydride copolymer microspheres, a compound selected from at least one of long-chain aliphatic metal salts, long-chain aliphatic amides, and long-chain aliphatic bases, and an N-vinylamide polymer are mixed and reacted, followed by solid-liquid separation to obtain the composite antibacterial agent.
7. The preparation method according to claim 6, wherein, The amount of the organometallic salt is 0.1-5 parts by weight, the amount of the maleic anhydride copolymer microspheres is 0.05-5 parts by weight, the amount of the compound is 0.5-5 parts by weight, and the amount of the N-vinylamide polymer is 0.5-6 parts by weight.
8. The preparation method according to claim 7, wherein, The amount of the organometallic salt is 0.11-1 parts by weight, the amount of the maleic anhydride copolymer microspheres is 1.5-3.5 parts by weight, the amount of the compound is 1-2.5 parts by weight, and the amount of the N-vinylamide polymer is 1.5-4.5 parts by weight.
9. The preparation method according to any one of claims 6-8, wherein, The particle size of the maleic anhydride copolymer microspheres is 1000-1600 nm.
10. The preparation method according to claim 9, wherein, The particle size of the maleic anhydride copolymer microspheres is 1000-1500 nm.
11. The preparation method according to any one of claims 6-8, wherein, The conditions for the mixed reaction include: a reaction temperature of 70-90℃ and a reaction time of 20-70 min.
12. The application of the composite antibacterial agent according to any one of claims 1-5 in biodegradable plastics; in, The biodegradable plastic is selected from at least one of PBST, PBAT, PGA, PLA, PCL, PBSA, PBSL, PBS, PHA, and PPC.
13. An antibacterial biodegradable polyester composition, characterized in that, The composition includes a biodegradable copolyester, an antibacterial agent, an antioxidant, an anti-migration agent, and a hydrolysis inhibitor; The biodegradable copolyester has a melt index of 0.1-10 g / 10 min at 190 °C and a load of 2.16 kg; Based on 100 parts by weight of biodegradable copolyester, the amount of antibacterial agent is 0.05-5 parts by weight, the amount of antioxidant is 0.05-5 parts by weight, the amount of anti-migration agent is 0.001-0.1 parts by weight, and the amount of hydrolysis inhibitor is 0.1-5 parts by weight. The antibacterial agent is the composite antibacterial agent according to any one of claims 1-5.
14. The composition according to claim 13, wherein, Based on 100 parts by weight of the biodegradable copolyester, the amount of the antibacterial agent is 0.1-2 parts by weight; the amount of the antioxidant is 0.05-2 parts by weight; the amount of the anti-migration agent is 0.002-0.05 parts by weight; and the amount of the hydrolysis inhibitor is 0.5-2 parts by weight. And / or, the melt index of the biodegradable copolyester at 190°C and a load of 2.16 kg is 1-6 g / 10 min; And / or, the melt strength of the biodegradable copolyester is 0.05-0.5 N; And / or, the end carboxyl group content of the biodegradable copolyester is 2-20 mol%.
15. The composition according to claim 13 or 14, wherein, Based on 100 parts by weight of biodegradable copolyester, the amount of antibacterial agent is 0.2-1 parts by weight; the amount of antioxidant is 0.1-0.5 parts by weight. And / or, the melt strength of the biodegradable copolyester is 0.08-0.3 N; And / or, the end carboxyl group content of the biodegradable copolyester is 6-16 mol.
16. The composition according to claim 13, wherein, The anti-migration agent is selected from blocked polyisocyanates and / or fluorinated compounds; And / or, the hydrolysis inhibitor is selected from polycarbodiimide and / or monomeric carbodimethylamine.
17. The composition according to claim 16, wherein, The fluorinated compound is selected from ethers of α-hydro-ω-hydroxy polyethylene oxide and α-fluoro-ω-(2-hydroxyethyl)poly(difluoromethylene), (C2H4O). n (CF2) n At least one of C2H5FO, F(CF2CF2)3-8CH2CH2O(CH2CH2O)1-3H, F(CF2CF2)4O(CH2CH2O)6H, F(CF2CF2)3O(CH2CH2O)H, F(CF2CF2)O(CH2CH2O)8CH3 and F(CF2CF2)4CH2OCH2CH(OH)CH2O(CH2CH2O)4H; And / or, the monomeric carbodiamine is selected from at least one of dicyclohexylcarbodiimide, N,N'-diisopropylcarbodiimide, 2,2',6,6'-tetraisopropylcarbodiimide, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride.
18. The composition according to claim 13 or 14, wherein, The antioxidant is a hindered phenolic antioxidant and a phosphite antioxidant in a mass ratio of 1:3 to 3:1; And / or, the antibacterial agent further includes a natural antibacterial agent, wherein the mass ratio of the natural antibacterial agent to the composite antibacterial agent is 0.1-10:
1.
19. The composition according to claim 18, wherein the hindered phenolic antioxidant is selected from at least one of antioxidant 1010, antioxidant 3114, antioxidant 245 and antioxidant 330; And / or, the phosphite antioxidant may be selected from at least one of antioxidant 168, antioxidant 618, bis(2,4-dicumylphenyl)pentaerythritol-diphosphite, pentaerythritol diphosphite bisoctadecyl and antioxidant 2,2'-ethylidene di(4,6-di-tert-butylphenyl)fluorophosphite; And / or, the mass ratio of the natural antibacterial agent to the composite antibacterial agent is 0.4-2:
1.
20. The composition according to claim 13 or 14, wherein, The composition further includes a slip agent, wherein the amount of the slip agent is 0.01-5 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further comprises a chain extender, wherein the amount of the chain extender is 0.01-5 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further includes a blending reinforcement component, wherein the amount of the blending reinforcement component is 2-20 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further includes a nucleating agent, wherein the amount of the nucleating agent is 0.01-2 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further includes a dispersant, wherein the amount of the dispersant is 0.01-1 parts by weight relative to 100 parts by weight of the biodegradable copolyester.
21. The composition according to claim 20, wherein, The amount of the slip agent is 0.05-2 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further includes a chain extender, wherein the amount of the chain extender is 0.05-2 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further includes a blending reinforcement component, wherein the amount of the blending reinforcement component is 4-12 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further includes a nucleating agent, wherein the amount of the nucleating agent is 0.05-1 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further includes a dispersant, wherein the amount of the dispersant is 0.05-0.2 parts by weight relative to 100 parts by weight of the biodegradable copolyester.
22. The composition according to claim 20, wherein, The amount of the slip agent is 0.05-0.5 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further includes a chain extender, wherein the amount of the chain extender is 0.1-1 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further includes a blending reinforcement component, wherein the amount of the blending reinforcement component is 5-10 parts by weight relative to 100 parts by weight of the biodegradable copolyester; And / or, the composition further includes a nucleating agent, wherein the nucleating agent is used in an amount of 0.1-0.7 parts by weight relative to 100 parts by weight of the biodegradable copolyester.
23. The composition according to claim 20, wherein, The slip agent is selected from stearates and / or organic carboxylic acid amides; And / or, the chain extender is selected from at least one of styrene-glycidyl methacrylate copolymer, styrene-butyl acrylate-glycidyl methacrylate terpolymer, methylstyrene-methacrylate-glycidyl acrylate terpolymer, and styrene-methyl methacrylate-glycidyl methacrylate terpolymer; And / or, the blended reinforcing component is selected from at least one of polycaprolactone, polybutylene succinate, polyglycolic acid, polylactic acid, polyhydroxyalkanoates and polymethyl ethylene carbonate; And / or, the crystallizing nucleating agent is selected from at least one of hyperbranched polyamide, ethylene-methacrylate ionomer, diphenyl dihydrazide sebacate, diphenyl dihydrazide adipate, and zinc phenyl phosphate; And / or, the dispersant is selected from at least one of kaolin, mica, pyrope, clay, bauxite, titanium dioxide, basic magnesium carbonate, basic zinc carbonate, calcium carbonate, silicon dioxide, zinc borate, and iron oxide.
24. The composition according to claim 23, wherein, The slip agent is selected from at least one of calcium stearate, erucamide, oleamide, stearamide, stearic acid stearamide, and N,N'-ethylenebis-stearamide; And / or, the dispersant is kaolin.
25. A method for preparing an antibacterial biodegradable polyester material, characterized in that, The method includes: mixing the antibacterial biodegradable polyester composition and extruding and granulating it to obtain the antibacterial biodegradable polyester material; The antibacterial biodegradable polyester composition is the antibacterial biodegradable polyester composition according to any one of claims 13-24.
26. The preparation method according to claim 25, wherein, The conditions for extrusion granulation include: an extrusion temperature of 140-230℃ and a screw speed of 100-500 rpm.
27. The preparation method according to claim 25 or 26, wherein, The conditions for extrusion granulation include: an extrusion temperature of 150-180℃ and a screw speed of 150-250 rpm.
28. An antibacterial biodegradable polyester material prepared by any one of claims 25-27.
29. An antibacterial biodegradable polyester blown film, characterized in that, The blown film is made from the antibacterial biodegradable polyester material as described in claim 28.
30. The antibacterial biodegradable polyester blown film according to claim 29, wherein, The thickness of the antibacterial biodegradable polyester blown film is 5-100 μm; And / or, the tensile breaking stress of the antibacterial biodegradable polyester blown film is greater than or equal to 18 MPa; And / or, the longitudinal tensile strength of the antibacterial biodegradable polyester blown film is greater than or equal to 18 MPa, and the transverse tensile strength is greater than or equal to 16 MPa. And / or, the antibacterial biodegradable polyester blown film has a longitudinal elongation at break greater than or equal to 250% and a transverse elongation at break greater than or equal to 350%; And / or, the light transmittance of the antibacterial biodegradable polyester blown film is greater than or equal to 89%.
31. A method for preparing the antibacterial biodegradable polyester blown film according to claim 29 or 30, characterized in that, The method includes: blow molding the antibacterial biodegradable polyester material according to claim 28 to obtain the antibacterial biodegradable polyester blown film.
32. The preparation method according to claim 31, wherein, The conditions for blow molding include: a blown film temperature of 150-210℃; and a blow-up ratio of 1.5-3:
1.
33. The use of the antibacterial biodegradable polyester blown film of claim 29 or 30 in antibacterial packaging film bags.
Citation Information
Patent Citations
Composite material of Nano grains of silver and carriers of polymer microballons, and preparation method
CN101091898A
Polypropylene modified composition and modified polypropylene
CN109721813A